2022
DOI: 10.1021/acs.jmedchem.2c00972
|View full text |Cite
|
Sign up to set email alerts
|

Nitroimidazopyrazinones with Oral Activity against Tuberculosis and Chagas Disease in Mouse Models of Infection

Abstract: Tuberculosis and parasitic infections continue to impose a significant threat to global public health and economic growth. There is an urgent need to develop new treatments to combat these diseases. Here, we report the in vitro and in vivo profiles of a new bicyclic nitroimidazole subclass, namely, nitroimidazopyrazinones, against mycobacteria and Trypanosoma cruzi. Derivatives with monocyclic side chains were selective against Mycobacterium tuberculosis and were able to reduce the bacterial load when dosed or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Causes skeletal muscle fibrosis and spastic diplegia in hamsters [50]. Widely used as a model for drug testing in combination with BALB/c mice [25,[27][28][29]51]. 10 Causes gastrointestinal transit time delay in C3H/HeN mice [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Causes skeletal muscle fibrosis and spastic diplegia in hamsters [50]. Widely used as a model for drug testing in combination with BALB/c mice [25,[27][28][29]51]. 10 Causes gastrointestinal transit time delay in C3H/HeN mice [20].…”
Section: Resultsmentioning
confidence: 99%
“…Causes skeletal muscle fibrosis and spastic diplegia in hamsters [ 50 ]. Widely used as a model for drug testing in combination with BALB/c mice [ 25 , 27 29 , 51 ]. 10 Causes gastrointestinal transit time delay in C3H/HeN mice [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The solid-phase peptide synthesis (SPPS) was undertaken using standard SPPS protocols outlined by Amblard et al 13a and modified where appropriate using methods reported by Varamini et al 17 The Rink Amide resin was deprotected, and the first C-terminal amino acid, Fmoc-Phe-OH (25), was loaded onto the resin using the coupling reagent, benzotriazol-1-yloxytripyrrolidinophosphonium hexafluorophosphate (PyBOP, 26), together with N-hydroxybenzotriazole (HOBt).…”
Section: ■ Synthesismentioning
confidence: 99%
“…The seco -azacubane-isoniazid epimer 31 was subjected to a resazurin reduction microplate assay (REMA) to assess growth inhibition of M. tuberculosis . However, no inhibition was observed at the maximum concentration investigated (10 μg/mL).…”
Section: Biological Evaluationmentioning
confidence: 99%
“…The aryl ether moiety is ubiquitous in medicines, agrochemicals, and materials . For example, many top-selling drugs, such as Pramoxine, Nexium, Delamanid, Duloxetine, Guaifenesin, Naproxen, and Idalopirdine, contain an aryl ether moiety. Aryl ethers could be prepared by the Williamson ether synthesis, Mitsunobu reaction, and nucleophilic aromatic substitution .…”
mentioning
confidence: 99%